Meet the expert Heidi Helfand on dynamic reteaming - Helfand, Heidi (O'Reilly Media, Inc., 2020)
"Your team will change whether you like it or not. People will come and go. Your company might double in size or even be acquired. The good news: successfully managing this change can lead to better productivity and more innovation. Join us for this edition of Meet the Expert with Heidi Helfand to learn techniques for reteaming effectively. Engineering leaders will discover how to catalyze team change to reduce the risk of attrition, learning and career stagnation, and the development of knowledge silos. Heidi shares patterns based on research into several well-known software companies that will help you effectively integrate new hires into an existing team, manage a team that's lost members, and deal with unexpected change. You'll learn when to split a team, how to isolate teams for focused innovation, how to rotate team members for knowledge sharing, how to break through organizational apathy, and much more"--Resource description page
Title from resource description page (Safari, viewed December 7, 2020)
Keywords: Teams in the workplace; Supervision of employees; Organizational change; Équipes de travail; Personnel; Supervision; Changement organisationnel